Keabsahan Perjanjian Lisan Menurut Hukum Perdata di Indonesia - Bella Putri Sakinah (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
In everyday life, the practice of making agreements is often done simply without written form, especially in social interactions and informal economic activities. This raises legal questions about whether agreements made orally have valid legal force. This study aims to understand the legal position of oral agreements from the perspective of Indonesian civil law, especially regarding the requirements for the validity of an agreement based on the provisions of Article 1320 of the Civil Code (KUHPerdata). This study uses a normative juridical method, with an approach to laws and legal doctrine. The results of the study show that even though they are not made in writing, oral agreements are still valid as long as they meet the applicable legal requirements. However, the problem that often arises lies in the difficulty of proof when peace occurs. Therefore, it is important for parties to consider written records as a form of legal protection.